2013
DOI: 10.1063/1.4791693
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical characteristics of high-k/metal gate metal oxide semiconductor capacitors fabricated on flexible, semi-transparent silicon (100) fabric

Abstract: Structural and electrical characteristics of high-k/metal gate metal oxide semiconductor capacitors fabricated on flexible, semi-transparent silicon (100)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…In the past, on ultra-thin silicon with deterministic pattern of porous network of vertical micro-air channels, we have demonstrated various functioning physical electronics including MIMCAPs, 41,42 MOSCAPs, [43][44][45][46] MOSFETs, 47 FinFETs 48,49 (including high temperature study 50 ), thermoelectric generators (TEGs), 51 and memristors 52 and have also reported their full performance analysis (both electrical and mechanical) [41][42][43][44][45][46][47][48][49][50][51][52] and their long term mechanical and electrical reliability and stability. 42,43,49,50,53 In all of those studies we consistently observed no noticeable electrical performance variation due to the ultra-thin silicon.…”
Section: A Fabricationmentioning
confidence: 99%
“…In the past, on ultra-thin silicon with deterministic pattern of porous network of vertical micro-air channels, we have demonstrated various functioning physical electronics including MIMCAPs, 41,42 MOSCAPs, [43][44][45][46] MOSFETs, 47 FinFETs 48,49 (including high temperature study 50 ), thermoelectric generators (TEGs), 51 and memristors 52 and have also reported their full performance analysis (both electrical and mechanical) [41][42][43][44][45][46][47][48][49][50][51][52] and their long term mechanical and electrical reliability and stability. 42,43,49,50,53 In all of those studies we consistently observed no noticeable electrical performance variation due to the ultra-thin silicon.…”
Section: A Fabricationmentioning
confidence: 99%
“…This simple but adaptable process is capable of transforming from semiconducting materials, such mono-crystalline bulk silicon (100), silicon germanium (SiGe) and III-V compound semiconductors, to dielectric and insulating materials. Several flexible electric devices have been demonstrated through this process, including metal-oxide-semiconductor capacitors (MOSCAPs), field effect transistors (MOSFETs), metal-insulator-metal capacitors (MIMCAPs) and state-of-the-art 3D-fin field effect transistors (FinFETs) [20][21][22][23][24][25]. Additionally, alternative flexible devices have been also demonstrated such micro electromechanical systems (MEMS), memory systems, and energy harvesting and storage devices [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…As was previously reported, the variety of devices on our flexible Si platform exhibits no significant degradation comparing to the conventional bulk devices. [20][21][22][23][24][25] In this work, we assess the impact of mechanical anomaly (bending radius, bending cycles, and hold time at a certain bending condition) on the characteristics of the metaloxide-semiconductor capacitors (MOSCAPs) representing a basic element of electronic circuits built on our flexible Si platform.…”
mentioning
confidence: 99%